Efektifitas Nutrisi Hidroponik AB MIX Sebagai Larvasida Alternatif Larva Nyamuk Aedes aegypti - Yauwan Tobing Lukiyono; Vella - Rohmayani (Universitas Muhammadiyah Surabaya, 2022)
ABSTRACT Hydroponics is a technique for cultivating vegetable and fruit plants. The principle of hydroponic technique is the provision of nutrient solution as a source of plant nutrients. These plants are grown in certain media using water instead of soil. The presence of stagnant water in hydroponic techniques can be a breeding place for Aedes aegypti larvae. Aedes aegypti mosquito can do as a vector for dengue fever. Dengue fever is still a public health problem today. The purpose of this study was to analyze the potential of AB mix as a nutrient for hydroponic plants as larvicides of the Aedes aegypti mosquito.This research was a pure experimental research. The research design used a pre post only group design. The research sample was F3 larvae of Aedes aegypti instar III. The research variables were the mortality of Aedes aegypti larvae and variations in the concentration of AB mix. The test was repeated 10 times. Data were analyzed using one-way ANOVA. Based on the results obtained in all treatments there was death or mortality of mosquito larvae. The administration of 75% AB Mix with a duration of 70 minutes is the most optimal treatment to eradicate Aedes aegypti mosquito larvae. So, it can be concluded that AB Mix can be used as an alternative larvicide to eradicate Aedes aegypti mosquito larvae. Keywords : AB Mix, mortalitas dan Larva Aedes aegypti